A Novel Effector Gene SCRE2 Contributes to Full Virulence of Ustilaginoidea virens to Rice - Fang, Anfei; Gao, Han; Zhang, Nan; Zheng, Xinhang; Qiu, Shanshan; Li, Yuejiao; Zhou, Shuang; Cui, Fuhao; Sun, Wenxian (Frontiers in Microbiology, 2019)
Ustilaginoidea virens, the causal agent of rice false smut, has become one of the most devastating rice pathogens worldwide. As a group of essential virulence factors, the effectors in the filamentous fungus might play central roles in the interaction between plants and pathogens. However, little is known about the roles of individual effectors in U. virens virulence. In this study, we identified and characterized a small secreted cysteine-rich effector, SCRE2, in U. virens. SCRE2 was first confirmed as an effector through yeast secretion, protein localization and translocation assays, as well as its expression pattern during U. virens infection. Transient expression of SCRE2 in Nicotiana benthamiana suppressed necrosis-like defense symptoms triggered by the mammalian BAX and oomycete elicitin INF1 proteins. The ability of SCRE2 to inhibit immunity-associated responses in N. benthamiana, including elicitor-triggered cell death and oxidative burst, is further defined to a small peptide region SCRE268-85 through expressing a series of truncated proteins. Convincingly, ectopic expression of SCRE2 in the transgenic rice cells significantly inhibited pathogen-associated molecular pattern-triggered immunity including flg22- and chitin-induced defense gene expression and oxidative burst. Furthermore, the scre2 knockout mutant generated by the CRISPR/Cas9 system greatly attenuated in U. virens virulence to rice. Collectively, this study indicates that the effector SCRE2 is able to inhibit plant immunity and is required for full virulence of U. virens.